Students’ Creative Process in Writing a Feature: A Critical Analysis - Sasmita, Kadek Sathya (Journal of Educational Study, 2023)
In creative writing, the process of student develops the idea into a piece of features becomes an emphasis rather than the final result. The student who made a feature writing certainly needs to pass the process in order to make a good feature writing. This study aimed at analysing the creative process of that experienced by students in writing feature writing in creative writing class and their creative process that is reflected in their creative writing. It was a qualitative study especially a case study, in which the data were collected and described through phenomena that were found on the creative process of the student in creating their feature writing. The finding of the study revealed all of the students passed seven stages of the creative process. All of the seven stages were preparation, planning, incubation, beginning flowing, breakthrough, and titling. One of the respondents missed the planning stages because that respondent write the feature directly without making a draft first. The result of the study implies that creative writing is different from common writing in terms of the process. Teachers are encouraged to help students to give suggestions and feedback during students’ creative writing process.